The Relationship between the Frequency of Coughs and Colds on the Growth of Toddlers Aged 1-5 Years at the Malawaken Village Health Post - Dewi Zulkiah; Widia Shofa Ilmiah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Mothers of newborns and children under the age of five frequently regard coughs and colds as minor ailments. This illness can actually progress to more severe issues, such as a weakened immune system, which makes kids more prone to infections that may eventually impair their cognitive development and growth. Using an analytical observational design with a cross-sectional approach, this study seeks to examine the correlation between the number of coughs and colds and the development of toddlers. All toddlers between the ages of 1 and 5 at the Malawaken Village Health Post are included in the population; 30 children were subjected to total sampling. With a correlation coefficient of 0.385 and a significance level of p = 0.026 (p < 0.05), which suggests a positive and substantial correlation, the Kendall’s tau-b correlation test was used to conduct data analysis. This implies that the effect on a toddler’s growth, particularly on body weight, becomes more evident as they have more coughs and colds